Karl Jaspers' Philosophy and psychopathology - Fuchs, Thomas; Breyer, Thiemo; Mundt, Christoph (Springer New York, 2013)
In this book, international scholars examine the basic psychopathological concepts of Karl Jaspers and their anthropological roots in light of modern research paradigms. It offers new perspectives for the analysis of consciousness and its disorders
Description based upon print version of record
Keywords: Electronic books; Aufsatzsammlung; Psychopathologie; Philosophie; Jaspers, Karl